Effect of temperature on the melt flow length of injection molding part - Trần Minh Thế Uyên; Phan Thế Nhân; Phạm Sơn Minh; Đỗ Thành Trung (Journal of Technical Education Science, 2014)
In injection molding field, the proper temperature helps the filling of melt becomes easier, reduces many troubles of molding par, especially with the thin wall part or the high aspect ratio L/T part. In this study, for observing the influence of mold temperature on the melt flow length, the water will be heated to the target temperature, then, this hot water will be flowed into the channel of mold plate, which will change the mold temperature. After the molding process finished, the length of molding part will be measured and compared. The result shows that higher mold temperature, longer flow length can be reached. In addition, in this paper, the Moldflow software will be used for simulating the filling process under different mold temperatures. The simulation result proves that the filling step can be predicted precisely by this software.